Work Family Conflict, Individual Characteristic, and Teamwork on Employee Performance in Transportation Sector - Dwi Fajar Andriani, Retno; Sumartik, Sumartik; Firdaus, Vera (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This research aims to identify and anlyze Work Family Conflict, Individual Characteristic, and Teamwork on Work Performance in the transportation sector. This research using a quantitative approach. The sampling using the total sample technique with the number of respondents as many as 60 respondents from Dinas Perhubungan Surabaya City Bidang Angkutan. The Data collection techniques using questionnaires distributed through questionnaires. The data analysis technique in this study used multiple linear regression analysis. Data processing in this study used the SPSS 25 software program (statistical program for the social sciences). The results of this study show that the work family conflict has a negative and significant effect on employee performance, individual characteristics has a positive and significant effect on employee performance, team work has a positive and significant effect on employee performance work family conflict, individual characteristic, teamwork simultaneously have a positive and significant effect on employee performance.